The Role of Islamic Boarding School Cooperatives in Developing the Entepreneurial Skills of Students (Case Study: Al Azhar Azzayyadiyah Islamic Boarding School) - Mawaddah Mawaddah; Fahrurrozi Fahrurrozi; Ridan Muhtadi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Islamic boarding schools not only function as religious educational institutions, but also have a strategic role in producing economically independent students. This study aims to analyze the role of the Al Azhar Azzayyadiyah Islamic Boarding School Cooperative in developing students' entrepreneurial skills. This study uses a qualitative approach, with a case study approach, data collected through observation, in-depth interviews, and documentation. The results show that the Islamic boarding school cooperative functions as an experiential learning vehicle that equips students with technical skills (sewing, batik, knitting, and marketing), while also developing soft skills such as discipline, communication, leadership, and responsibility. These findings also show an increase in students' self-efficacy in managing businesses, in contrast to previous studies that highlighted students' weak self-confidence. This study proves that Islamic boarding school cooperatives are not only economic units, but also strategic educational tools in empowering students. These findings emphasize the importance of integrating cooperative programs into non-formal education to produce independent students who are ready to compete in the business world. This research contributes to the development of religious community-based entrepreneurship education theory. In practice, this research strengthens the position of Islamic boarding schools as agents of local economic development through systematic and sustainable empowerment of students.